THE IMPACT OF COVID-19 PANDEMIC TO PURCHASING BEHAVIOR OF COASTAL COMMUNITIES IN LOCAL WET MARKET: CASE STUDY IN SMALL ISLANDS REGION - Frischilla Pentury (Universitas muhammadiyah malang, 2021)
The Covid-19 pandemic has had a significant impact on all aspects of communal life, including consumer purchasing habits. The issues confronting tiny island locations in dealing with the Covid-19 pandemic are more complex due to the lack of other means of satisfying daily necessities, in comparison to areas in larger cities that rely on internet shopping and/or delivery services for acquiring basics. The goal of this study is to examine the purchasing habits of coastal residents in two Kei Islands markets. Additionally, this study will look at the elements that influence purchasing behavior during a pandemic. The data gathering approach for this study is a purposive sample with a total of 206 respondents. The data collection instrument is a questionnaire. Logistic regression was utilized to analyze the data in this study. The study's findings indicate that both the intention to attend and the number of visits to the market have reduced in comparison to pre-pandemic levels. Additionally, the comfort factor, the fulfillment of wants, and health procedures all have a significant impact on how this community behaves. Thus, the primary policy relevance of these findings is the government's involvement in ensuring the comfort and safety of coastal people when they engage in purchasing activities in these two markets, one of which is the enforcement of health protocol.